Rescue of αB Crystallin (HSPB5) Mutants Associated Protein Aggregation by Co-Expression of HSPB5 Partners. - Rasha M Hussein; Ivor J Benjamin; Harm H Kampinga (PLoS ONE, 2015)
HSPB5 (also called αB-crystallin) is a ubiquitously expressed small heat shock protein. Mutations in HSPB5 have been found to cause cataract, but are also associated with a subgroup of myofibrillar myopathies. Cells expressing each of these HSPB5 mutants are characterized by the appearance of protein aggregates of primarily the mutant HSPB5. Like several members of the HSPB family, HSPB5 can form both homo-oligomeric and hetero-oligomeric complexes. Previous studies showed that co-expression of HSPB1 and HSPB8 can prevent the aggregation associated with the HSPB5 (R120G) mutant in cardiomyocytes and in transgenic mice. In this study, we systematically compared the effect of co-expression of each of the members of the human HSPB family (HSPB1-10) on the aggregation of three different HSPB5 mutants (R120G, 450 Δ A, 464 Δ CT). Of all members, co-expression of HSPB1, HSPB4 and HSPB5 itself, most effectively prevent the aggregation of these 3 HSPB5 mutants. HSPB6 and HSPB8 were also active but less, whilst the other 5 HSPB members were ineffective. Co-expression of Hsp70 did not reduce the aggregation of the HSPB5 mutants, suggesting that aggregate formation is most likely not related to a toxic gain of function of the mutants per se, but rather related to a loss of chaperone function of the oligomeric complexes containing the HSPB5 mutants (dominant negative effects). Our data suggest that the rescue of aggregation associated with the HSPB5 mutants is due to competitive incorporation of its partners into hetero-oligomers hereby negating the dominant negative effects of the mutant on the functioning of the hetero-oligomer.